2018
DOI: 10.1088/1674-1056/27/7/074102
|View full text |Cite
|
Sign up to set email alerts
|

Reliable approach for bistatic scattering of three-dimensional targets from underlying rough surface based on parabolic equation

Abstract: A parabolic equation (PE) based method for analyzing composite scattering under an electromagnetic wave incidence at low grazing angle, which composes of three-dimensional (3-D) electrically large targets and rough surface, is presented and discussed. A superior high-order PE version is used to improve the accuracy at wider paraxial angles, and along with the alternating direction implicit (ADI) differential technique, the computational efficiency is further improved. The formula of bistatic normalized radar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Theoretically, owing to the compensation for spatial parabolic phase gradients, the reflective vortex beams will propagate along the normal direction rather than oblique direction. [22] The designing process of metasurface reflector is depicted in Fig. 4(c).…”
Section: Configurations and Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, owing to the compensation for spatial parabolic phase gradients, the reflective vortex beams will propagate along the normal direction rather than oblique direction. [22] The designing process of metasurface reflector is depicted in Fig. 4(c).…”
Section: Configurations and Simulationsmentioning
confidence: 99%
“…With the development of artificial materials, metasurface has become an alternative tool to design OAM generator due to the advantages of negligible thickness and huge manipulation flexibility. [1,2,5,[11][12][13][14][15][16][17][18][19][20][21][22] Unfortunately, the mechanism of generating OAM by the aforementioned strategies introduces a twist phase profile. Therefore, it is hard to achieve vortex beams with versatile topological charges in a shared aperture.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic (EM) scattering from targets in extra-low-altitude and environments could be abstracted into scattering problems of radar targets above rough surface. The conventional farfield scattering from rough surface and targets has been widely investigated in the past decades, [1][2][3][4] but research on near-field scattering from targets and surface has rarely been reported yet, which is really a hot topic and challenging issue. The nearfield scattering from targets in free space is computed by using accurate multilevel fast multi-pole method (MLFMM), and application advices on near-field characteristics were given in Ref.…”
Section: Introductionmentioning
confidence: 99%